Clinical Profile and Short-Term Outcome of Malaria in Febrile Under-Five Children in a Secondary Health Facility - Oluwafemi RO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Malaria remains an essential tropical protozoal disease, affecting both young and old. It manifests in complicated and uncomplicated forms with more grave consequences among Under-five children. Objective: To describe malaria's clinical profile and short-term outcomes in Under-five children in a secondary health facility in southwest Nigeria. Methods: This was a hospital-based and cross-sectional study. Five hundred children under the age of five years who presented with fever at the health facility were recruited into the study. The clinical manifestations were documented, and blood samples were examined for malaria parasitaemia. Results: Forty-eight children (9.6%) of the study subjects were neonates, 195 (39%) were infants, and the remaining 257 (51.4%) were aged 12 months to 5 years. One hundred and two (39.1%) of the 261 children positive for malaria presented with uncomplicated malaria, while 159 (60.9%) of this population had various complications. The overall mortality from malaria was 5.0%. Conclusion: More than 60% of the infected children had complications of malaria, and mortality was mainly due to late presentation. Therefore, malaria preventive strategies should be part of ongoing health interventions.